The Impact of Protocol Assignment for Older Adolescents with Hodgkin Lymphoma - Pieters, Richard S.; Wagner, Henry; Baker, Stephen; Morano, Karen; Ulin, Kenneth; Cicchetti, Maria Giulia; Bishop-Jodoin, Maryann; FitzGerald, Thomas J. (Frontiers in Oncology, 2014)
Background and Purpose: Hodgkin lymphoma (HL) treatment has evolved to reduce or avoid radiotherapy (RT) dose and volume and minimize the potential for late effects. Some older adolescents are treated on adult protocols. The purpose of this study is to examine the protocol assignment of older adolescents and its impact on radiation dose to relevant thoracic structures. Materials and Methods: Cooperative group data were reviewed and 12 adolescents were randomly selected from a pediatric HL protocol. Treatment plans were generated per one pediatric and two adult protocols. Dose volume histograms for heart, lung, and breast allowed comparison of radiation dose to these sites across these three protocols. Results: A total of 15.2% of adolescents were treated on adult HL protocols and received significantly higher radiation dosage to heart and lung compared to pediatric HL protocols. Adolescents treated on either pediatric or adult protocols received similar RT dose to breast. Conclusion: Older adolescents treated on adult HL protocols received higher RT dose to thoracic structures except breast. Level of nodal involvement may impact overall RT dose to breast. The impact of varying field design and RT dose on survival, local, and late effects needs further study for this vulnerable age group. Adolescents, young adults, Hodgkin lymphoma, RT, clinical trials